Efficacy of different commercial phytase sources and development of a phosphorus release curve - Jones, C.K.; Ratliff, B.W.; Horn, N.L.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments used 184 pigs (PIC, 22.7 and 21.3 lb BW, respectively) to develop an available P (aP) release curve for commercial phytase products. In Exp. 1 and 2, pigs were fed a basal diet (0.06% aP) and 2 levels of added aP from inorganic P (monocalcium P) to develop a standard curve. In Exp. 1, 100, 175, 250, or 500 phytase units (FTU)/kg OptiPhos (Enzyvia LLC, Sheridan, IN) or 200, 350, 500 or 1,000 FTU/kg Phyzyme XP (Danisco Animal Nutrition, Marlborough, UK) was added to the basal diet. In Exp. 2, 250, 500, 750, or 1,000 FTU/kg OptiPhos; 500, 1,000, or 1,500 FTU/kg Phyzyme XP; or 1,850 or 3,700 phytase units (FYT)/kg Ronozyme P (DSM Nutritional Products, Basel, Switzerland), was added to the basal diet. Manufacturer-guaranteed phytase levels were used in diet formulation. Diets were analyzed for phytase using both the Phytex and AOAC methods. Pigs were blocked by sex and weight and allotted to individual pens with 8 pens per treatment. Pigs were euthanized on d 21, and fibulas were analyzed for bone ash. In Exp. 1, pigs fed increasing monocalcium P had improved (linear; P = 0.01) ADG, G/F, and percentage bone ash. Similarly, pigs fed increasing monocalcium P in Exp. 2 tended to have improved (quadratic; P = 0.09) ADG in addition to significantly improved (linear; P ≤ 0.001) G/F and percentage bone ash. In Exp. 1, pigs fed increasing OptiPhos had increased (linear; P ≤ 0.02) ADG, G/F, and percentage bone ash. Likewise, pigs fed increasing OptiPhos in Exp. 2 had improved (linear; P ≤ 0.001) ADG and G/F, as well as increased (quadratic; P ≤ 0.001) percentage bone ash. In Exp. 1, pigs fed increasing Phyzyme XP had increased (linear; P ≤ 0.04) ADG and G/F and tended to have improved (linear; P = 0.06) percentagebone ash. Pigs fed increasing Phyzyme XP in Exp. 2 had increased (quadratic; P ≤ 0.001) G/F and percentage bone ash. In Exp. 2, pigs fed increasing Ronozyme P had improved (linear; P ≤ 0.001) ADG in addition to increased (quadratic; P ≤ 0.03) G/F and percentage bone ash. When AOAC analyzed values and bone ash are used as the response variable, aP release for up to 1,000 FTU/kg of Escherichia coli-derived phytases (OptiPhos and Phyzyme XP) can be predicted by the equation (y = -0.000000125x2 + 0.000236245x + 0.015482000), where x is the phytase level in the diet.
Keywords: Bone strength; Phytase; Phytase source; Swine